The Effect of Different Water Solution on the Electrical Conductivity of Polyester Reinforced With Waste Aluminum - Mohammad, Shayma H. (Nahrain University College of Engineering Journal, 2015)
In this work, we studied the electrical conductivity behavior of waste Al reinforced polyester composite material in different solutions (distilled water, tap water &3.5%NaCl) with a weight fraction (5, 15, 30 &45) was investigated for (6) weeks immersion time. The results exhibited that increasing in electrical conductivity with increasing in immersion time, also Maximum value of electrical conductivity was recorded at immersion in 3.5% NaCl solution. However electrical conductivity increases with increasing in weight fraction of waste aluminum due to opening path of electrons thus electrical conductivity will be increased.